Pengaruh kepemimpinan kepala sekolah, komunikasi dan sertifikasi guru terhadap persepsi kinerja guru - Noersanti, Lina; Juniarti, Juniarti; Hastin, Abiyyah (Jurnal STEI Ekonomi, 2023)
This study aims to find out the influence of the principal's leadership, communication and teacher certification on the perception of teacher performance at SDN Pisangan Timur 01 Pagi. This research approach is quantitative with a correlation model. Data were obtained using survey methods. The population in this study are teachers at SDN Pisangan Timur 01 Pagi, a total of 30 teachers. The sample in this study is a saturated sample. The analysis used is SEM-PLS which consists of outer model, inner model and hypothesis testing using SmartPls 3.0 software. The results of this study show that the principal's leadership has no effect on teacher performance. Communication and teacher certification have an influence on teacher performance. Good communication between fellow teachers and their leaders can improve the performance of teachers in schools. The benefits provided through certification can motivate a teacher to be a better teacher for his students.